2021
DOI: 10.1097/gox.0000000000003656
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Elective Cleft Surgery in Low- and Middle-income Countries

Abstract: Background: The COVID-19 pandemic disrupted health systems worldwide, including in low- and middle-income countries (LMICs). Many countries limited the delivery of elective surgery. To date, COVID-19’s impact on elective surgery in LMICs has been unquantified. We use operative data from a large international non-government cleft organization to compare case volume for 2019 and 2020 to quantify the impact of COVID-19. Methods: Smile Train supports a partner network of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Although there was no significant outcome, the psychological impacts to patients and their families must be considered, especially without knowing when the pandemic would end, and patients under the age of 5 not eligible to receive a COVID-19 vaccine. [5][6][7][8] Other studies, such as the study done by Vander Burg and colleagues (2021) showed that in the period of January to December 2020, the number of cleft repair surgeries declined to as much as 25,444 cases. 6 Patients are predominantly children and added to the number of 60,000 people left with untreated cleft lip palate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there was no significant outcome, the psychological impacts to patients and their families must be considered, especially without knowing when the pandemic would end, and patients under the age of 5 not eligible to receive a COVID-19 vaccine. [5][6][7][8] Other studies, such as the study done by Vander Burg and colleagues (2021) showed that in the period of January to December 2020, the number of cleft repair surgeries declined to as much as 25,444 cases. 6 Patients are predominantly children and added to the number of 60,000 people left with untreated cleft lip palate.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Other studies, such as the study done by Vander Burg and colleagues (2021) showed that in the period of January to December 2020, the number of cleft repair surgeries declined to as much as 25,444 cases. 6 Patients are predominantly children and added to the number of 60,000 people left with untreated cleft lip palate. January to April 2020 showed the most significant decline in surgeries, while numbers then started to increase over May to December 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic has undoubtedly exacerbated the backlog of healthcare interventions for children born with CL/P, as they are for the most part regarded as planned elective procedures, although the magnitude of these delays on a global scale is yet to be fully appreciated ( Stoehr et al, 2021 ). Projections using data from 67 LMICs estimated 25,000 fewer cleft operations performed during 2020 compared to 2019 ( Vander Burg et al, 2021 ). In Peru, children born with CL/P were having primary reconstructions at a significantly older age during the pandemic when compared to a prepandemic cohort, with delays most marked in primary cleft lip and nose reconstruction ( Rossell-Perry and Gavino-Gutierrez, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…They report that they have over 10,000 patients awaiting treatment [ 3 ]. One recent article using data from Smile Train found that there was a 31% reduction in procedures to correct cleft palate between 2019 and 2020 [ 4 ]. With the arrival of the COVID-19 vaccines, humanitarian organizations should be able to increase the volume of cleft palate procedures performed.…”
mentioning
confidence: 99%